PENDAMPINGAN DESAIN DAN PENGEMBANGAN PACKAGING KERUPUK IKAN PINDANG DI DESA SUKAJADI KECAMATAN CARITA - Wahyiah, Ita Rosita; Rahayu, Luis Fiska; Arasid, Mohamad Ikrom; Arifin, Suherman; Rendiyani, M; Ichwana, Cahya Tri; Sabrina, Ina; Destriana, Halizah; Aulia, Dita; Arif, Khaerul (UNIVERSITAS SERAMBI MEKKAH, 2024)
KKM UNIBA Group 63 provided assistance in the design and development of packaging for pindang fish crackers in Sukajadi Village, Carita District, Pandeglang Regency as part of efforts to empower the local community economy with a focus on increasing the added value of local products. Pindang fish crackers, as one of the leading products from the village, has a wide market potential, but the main challenge faced is the packaging design that is less attractive and not in accordance with modern marketing standards. This service aims to provide support in terms of packaging design and development of pindang fish crackers to increase market attractiveness and expand distribution reach. The methods used include packaging design needs analysis, packaging design training, and new packaging implementation. The training process involved understanding the design concept, selecting appropriate packaging materials, and printing techniques. The results of the mentoring showed that the new packaging design successfully increased the visual appeal of the product, clarified product information, and improved quality perception in the eyes of consumers. The newly designed packaging also provides better protection to the product during the distribution process. With the attractive and functional packaging, sales of pindang fish crackers have increased significantly, and the product has successfully entered a wider market both at the local and regional levels.